Effect of bumper thickness with collision simulation of passenger vehicles - ERSOY, SEZGİN (My University, 2023)
The finite element method is the most common method used to solve engineering and mathematical model problems. Related solution areas include structural analysis, heat transfer, mass transport and electromagnetic potential. FEM is a specific numerical method used to solve partial differential equations in two or three space variables. To solve a problem, FEM breaks up a large system into smaller, simpler parts called finite elements. First, a three-dimensional model of the system to be analyzed is produced. While defining the model, the materials and connection types found in the model are also deter-mined. Afterwards, the model is divided into small parts and analyzed under specified conditions. A crash test will be conducted in this study. For this, the conditions of the vehicle parts will be examined by hitting a wall under the conditions of which the model design of the vehicle is determined. Crash tests were carried out for two different bumper thicknesses on the same vehicle and the test results were examined. The vehicle speed is modeled as 20 m/s in the simulation carried out from the moment of impact until 0.14 seconds later. The effect of buffer thickness on axial displacements at impact and energy changes are presented.
Keywords: Makina Mühendisliği; Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Mechanical Engineering; Metallurgical and Materials Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; METALLURGY & METALLURGICAL ENGINEERING; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Physical Sciences